Aspectos de uma história da cidade e da educação em Marília/SP - Conceição, Aline de Novaes (Editora Oficina Universitária, 2023)
This book brings to the reader, in a pleasant way, the recovery, analysis and presentation of a research instrument in which publications dealing with education in the newspaper O Alto Cafezal, edited in the city of Marília/SP, are highlighted, the author focuses on the period from 1928 to 1933. To this end, he searched the archives of the Organizing Committee of the Historical Records of the City Council and of the City of Marília/SP and of the Library "Councilman Rangel Pietraróia", custodians of documents, dissertations, theses, books, newspapers, audiovisual material, among others, which has the city of Marília/SP as its main theme. She elaborated 295 references of texts on education, hard work that will certainly guide and subsidize other researches in the area. It also provides an overview of the city's history and how school education has developed, with the press as an important vehicle in this development, opening spaces for various publications, including texts by students.